2011
DOI: 10.1080/03014223.2011.584541
|View full text |Cite
|
Sign up to set email alerts
|

Survey duration and season influence the detection of introduced eastern rosella (Platycercus eximius) in New Zealand

Abstract: Reliable survey methods for detection are critically important for the monitoring and management of exotic species. The eastern rosella (Platycercus eximius), a broad-tailed parakeet endemic to southeastern Australia, was introduced to New Zealand a century ago and is now geographically widespread. We studied the necessary timeframe for surveying the eastern rosella within its introduced range, testing the hypothesis that there are seasonal differences in the likelihood of detection. Although our comparisons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Counting birds in residential areas has a number of challenges, in particular physical barriers (e.g., fences, buildings), which prevent free movement of researchers through the landscape and reduce the probability of detecting birds (54). Because of this we used point counts from a fixed location, with a 10-min duration intended to increase detectability of birds that were blocked from sight (55,56). A point was chosen on the study property that afforded the widest view of the surrounding area.…”
Section: Methodsmentioning
confidence: 99%
“…Counting birds in residential areas has a number of challenges, in particular physical barriers (e.g., fences, buildings), which prevent free movement of researchers through the landscape and reduce the probability of detecting birds (54). Because of this we used point counts from a fixed location, with a 10-min duration intended to increase detectability of birds that were blocked from sight (55,56). A point was chosen on the study property that afforded the widest view of the surrounding area.…”
Section: Methodsmentioning
confidence: 99%
“…Paquet et al 2006, Shahabuddin & Kumar 2007, Bonthoux & Balent 2012, the expectation being that detectability will initially be low, but will increase after the birds have 'settled-down' following the initial disturbance caused by the observer's arrival (Bibby et al 2000), hence decreasing the probability of false absences being recorded. Whilst there is some evidence that detection can be lower in a SDP (Galbraith et al 2011), there is also evidence that its inclusion may underestimate abundance (Lee & Marsden 2008). Furthermore, other studies have indicated that shorter count durations may be the most appropriate for estimating local population size and for modelling bird distributions, either with (Bonthoux & Balent 2012) or without (Cimprich 2009) a SDP.…”
Section: Please Scroll Down For Articlementioning
confidence: 94%